Strategi Komunikasi Penyuluh Agama Hindu Dalam Meminimalisir Konversi Agama Umat Hindu Di Kota Mataram - Pande Putu Dwi Telaksana; I Wayan Sumertha; I Wayan Wirata (Program Studi Magister S2 Ilmu Komunikasi Hindu Institut Agama Hindu Negeri Gde Pudja Mataram, 2020)
This research is directed to get a study of Communication Strategies of Hindu Religious Instructors in Minimizing the Conversion of Hindus in the City of Mataram. The problem revealed in this study is how is the form of communication of Hindu religious instructors in minimizing religious conversion, what are the supporting and inhibiting factors experienced by Hindu religious instructors in minimizing religious conversion, and how communication strategies are used by Hindu religious instructors in minimizing religious conversion in the City Mataram This type of research is qualitative research while the data obtained by the method of observation, interviews and documentation of literature, then the data is interpreted by giving meaning, explaining patterns and characteristics between various concepts. To get the patterns and characteristics it is supported by symbolic communication theory, attitude theory and communicative action theory. Some components that can be analyzed and concluded include: First, the form of communication of non-civil servant Hindu religious instructors in minimizing religious conversion to Hindus in the city of Mataram, namely by interpersonal and group communication; Second, supporters and obstacles that are faced by non-civil servant Hindu religion instructors in minimizing religious conversion, that is, religious conversion can no longer be seen as something normal, given the shift in belief in religious teachings, where the behavior of some converts causes others to be influenced. This is very worrying for the further development of Hinduism, where the community is a heterogeneous society or has a high level of diversity and the role of the family is very important in anticipating the conversion of religion; Third, the material mastery strategy, communication skills, and family roles carried out by non-civil servant Hindu religious instructors in minimizing religious conversion can be explained in the implementation of guidance and coaching in the form of dharma discourse and dharmatula which are carried out every month, where the communication process of a Hindu non-religious instructor Civil servants need a strategy in the delivery of material with the aim that the Hindu instructors more easily deliver the material to Hindus in the city of Mataram.